2019
DOI: 10.1002/jee.20244
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scale student programs increase persistence in STEM fields in a public university setting

Abstract: Background: Louisiana State University's (LSU) STEM Talent Expansion Program (STEP) was established to increase students' persistence in first-year, declared engineering majors (a project priority), in science, technology, engineering, and math (STEM) majors (an NSF goal), and in all majors at LSU (an institutional goal). Over 8 years, 3,097 (27%) engineering students participated in one or more STEP activities including a residential college, a student mentoring program, an introductory engineering design cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 28 publications
(51 reference statements)
0
11
0
Order By: Relevance
“…For this reason, the term of STEM education should be taken with caution, since for some authors it is represented as a pedagogical action that prepares students for university engineering courses; others value it as a career path for an engineering profession, while others value it as a component of general education, when trying to improve STEM knowledge in the population [21]. The use of STEM in education involves students working as a team, to focus on problem solving, to increase decision making and creativity, to improve critical thinking and self-esteem, to acquire significant learning, to develop interaction between peers, to enhance self-efficacy, scientific identity and an attitude towards mathematics and science, to develop active learning, to improve reasoning skills, collaboration and the self-regulation of learning [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, the term of STEM education should be taken with caution, since for some authors it is represented as a pedagogical action that prepares students for university engineering courses; others value it as a career path for an engineering profession, while others value it as a component of general education, when trying to improve STEM knowledge in the population [21]. The use of STEM in education involves students working as a team, to focus on problem solving, to increase decision making and creativity, to improve critical thinking and self-esteem, to acquire significant learning, to develop interaction between peers, to enhance self-efficacy, scientific identity and an attitude towards mathematics and science, to develop active learning, to improve reasoning skills, collaboration and the self-regulation of learning [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Another approach to mitigate students' sense of isolation is to provide role models and mentors; this is particularly needed for female undergraduates in a male-dominated discipline (Matsui, Liu and Kane, 2003). Various studies describe positive outcomes of peer mentoring programs that pair new students with more senior students (Matsui, Liu and Kane, 2003;Nicklow, Kowalchuk, Gupta, Tezcan and Mathias, 2009), including benefits for the mentored students as well as the mentors themselves (Ikuma, Steele, Dann, Adio, Waggenspack, 2019). Ikuma et al (2019) report that a peer mentoring program for STEM students, in combination with other initiatives, significantly increased participants' persistence in engineering majors, in STEM majors, and at the university level compared to non-participating STEM students.…”
Section: Establishing Mentoring Structuresmentioning
confidence: 99%
“…A recent paper by LSU faculty and staff [11], found E 2 participation to have a significant impact on retention in engineering between the first and second year, although this trend was not seen in years 3-6. By comparing demographic and academic preparation variables, it was shown that students who attended E 2 were representative of the student population as a whole; this is important to note since the participants self-select for the camp.…”
Section: Resultsmentioning
confidence: 97%